Ultrasonography of the ankle joint - Jung Won Park; Sun Joo Lee; Hye Jung Choo; Sung Kwan Kim; Heui-Chul Gwak; Sung-Moon Lee (Ultrasonography, 2017)
Ankle disorders are a relatively common pathological condition, and ankle injuries account for approximately 14% of sports-related orthopedic emergency visits. Various imaging modalities can be used to make a diagnosis in cases of ankle pain; however, ultrasound (US) has several benefits for the evaluation of ankle pain, especially in the tendons, ligaments, and nerves of the ankle. The purpose of this article is to review the common causes of ankle pathology, with particular reference to US features. In addition, the importance of a dynamic evaluation and a stress test with US is emphasized.